Analisis Keputusan Pembelian Susu Hilo Platinum Ditinjau dari Kualitas Produk, Citra Merek, dan Pengetahuan Produk di Kota Ambon - Feky Reken; Siska Jeanete Saununu; Jacsy Tubalawanoy; Walter Tabelessy (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Sales and purchasing decisions of HiLo Platinum milk in Ambon City still show fluctuating conditions, indicating variations in consumer preferences and purchasing behavior. This condition encourages the need to study the factors that influence consumer purchasing decisions. This study aims to analyze the influence of product quality, brand image, and product knowledge on purchasing decisions of HiLo Platinum milk in Ambon City. The study used a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 119 respondents who had purchased or consumed HiLo Platinum milk using a purposive sampling technique. Data analysis was performed using multiple linear regression through Jamovi software. The results showed that product quality, brand image, and product knowledge have a positive and significant influence on purchasing decisions, with product quality being the most dominant variable. These findings indicate that health milk consumers tend to consider functional benefits, nutritional quality, and product understanding more than promotional factors alone in determining purchasing decisions. This research contributes to the development of consumer behavior studies and provides input for companies in designing marketing strategies that are oriented towards improving product quality, strengthening brand image, and consumer education.